Zapisz w jak najprostszej postaci .
a . ( a + b ) - ( 2a - b ) - ( a - 2b ) =
b . ( 3x - y + 1 ) - ( x + y ) + ( y - x ) =
c . - ( kx + ny ) - ( 3 kx + 2 ny ) + ( 5 kx - 3 ny ) =
d . ( 2 ab + a + 3 ) - ( 3 ab - a + 3 ) =
e . ( 4x^ - 3 x ) - ( x + 0,1 x^ ) - ( x^- 0,1 x ) =

Haah .. Dajee naj ; ]

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-07T15:31:43+02:00
A) (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=-2a+4b
b)(3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
c)-(kx+ny)-(3kn+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d)(2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
e)4x^-3x)-(x+0,1x^)-(x^-0,1x)=4x^-3x-x-0,1x^-x^+0,1x=-5,1x^-3,9x
jezeli ^ oznacza poteę to trzeba podstawic np do potedi 2
1 5 1